Dementia prevalence in a Lima, Peru urban community: door-to-door study - Custodio, Nilton (2008)
Objective: To determine the prevalence and types of dementia in a Lima’s urban community. Design: Bietapic conglomerate sampling. Setting: Private health institutions. Patients: Older than 65 years subjects. Interventions: In the Cercado de Lima district, 1 532 older than 65 years subjects randomly selected had brief neuropsychological evaluations including the Mini Mental State Examination (MMSE), drawing the Clock Test (PDR), and Pfeffer’s functional activities questionnaire (PFAQ). According to the results obtained, individuals were classified as selected or not selected. The group selected included those subjects presenting/displaying cognitive deterioration, who further had neurological and neuropsychological evaluations, laboratory tests and brain computed tomography (TC). Main outcome measures: Dementia prevalence. Results: We found 105 cases of dementia corresponding to 6,95% prevalence; Alzheimer’s disease was the most frequent diagnosis (56,2%). Dementia prevalence increased with age mainly in females. Logistic regression analysis showed that age, female sex and low education correlated with dementia prevalence. Conclusions: Dementia prevalence in this Peruvian population was 6,85%, and Alzheimer’s disease the most frequent diagnosis; age, female gender and low educative level factors correlated with this high prevalence.